Pengaruh Kualitas Produk, Harga, Dan Citra Merek Terhadap Keputusan Pembelian Produk Madlyson Di Distro Aztekline Tulungagung - Sumarsono, Rizkhi; Firdiansjah, Achmad; Respati, Harianto (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2018)
This study aims to describe each variable, analyze the effect of product quality, price, and brand image of influence on the intention of purchasing decision of Madlyson product, and analyze the dominant variable affecting purchase decision at Aztekline store in Tulungagung. This study was processed using quantitative approach with survey method, sampling was 60 respondents. Data were collected through observation and documentation. Hypothesis testing used multiple linear regression analysis techniques, including multiple correlation coefficient, multiple determination coefficient and t test (partial) and F (simultaneous) test. Then, the data obtained will be analyzed using SPSS software version 16 (Statistics Package for Social Sciences). Analyzer used consisted of: Analysis of validity and reliability, Test of Classic Assumption, Normality Test, Multicollinearity Test, Heteroskidastity Test. The results of the analysis show that product quality, price, and brand image simultaneously affect the purchase decision of the product. Partially, all independent variables significantly affect purchasing decisions. The dominant variable is the brand image (56.8%). The coefficient of determination (R2) shows that the independent variables studied can contribute to the dependent variable of 46.3% while the remaining 53.7% due to the contribution of outside research variables.